Hermeneutic Notion of a Human Being as an Acting and Suffering Person: Thinking with Paul Ricoeur - Wiercinski, Andrew (ETHICS IN PROGRESS, 2013)
Acting and suffering subjectivity makes a grand sujet in Ricoeur's philosophy. In his Time and Narrative Ricoeur created the notion of narrative identity which is an individual internalized and evolving life strory. The narrative alone might define the “who”. Whoever lives and exists, suffers. Ricoeur metaphorically defined life as a cloth. We can add, Wiercinski continues, that this cloth is woven with pain. It is pain which makes the cloth, and, at the same time, it is also a joy of the human condition. As humans, we are called to wear this cloth as well as to understand what does it mean - from the hermeneutic perspective.